The Role of Digital Emotional Branding in Enhancing Consumer Loyalty in the Platform-Based Online Culinary Industry - Sri Wahyuning (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
The rapid development of digital technology has transformed the culinary industry into a platform-based online ecosystem where competition is increasingly intense and consumer switching behavior is relatively high. In this context, brands are required not only to compete on functional aspects such as price and promotion, but also to build meaningful emotional connections with consumers through digital interactions. This study aims to analyze the role of digital emotional branding in enhancing consumer loyalty in the platform-based online culinary industry and to examine the mediating role of emotional attachment in this relationship. A mixed methods sequential explanatory design was employed, involving a quantitative survey of 250 active platform users analyzed using SEM-PLS, followed by in-depth interviews with 12 selected informants to enrich the interpretation of findings. The results indicate that digital emotional branding has a positive and significant effect on consumer loyalty, both directly and indirectly through emotional attachment as a mediating variable. These findings demonstrate that emotionally oriented digital strategies strengthen psychological bonds and long-term commitment in competitive platform environments. This study contributes theoretically by integrating digital branding and emotional attachment into a comprehensive model and offers practical implications for culinary businesses in designing more engaging and sustainable digital branding strategies.